Chromosome Organization in Early Meiotic Prophase - Grey, Corinne; de Massy, Bernard (Frontiers in Cell and Developmental Biology, 2021)
One of the most fascinating aspects of meiosis is the extensive reorganization of the genome at the prophase of the first meiotic division (prophase I). The first steps of this reorganization are observed with the establishment of an axis structure, that connects sister chromatids, from which emanate arrays of chromatin loops. This axis structure, called the axial element, consists of various proteins, such as cohesins, HORMA-domain proteins, and axial element proteins. In many organisms, axial elements are required to set the stage for efficient sister chromatid cohesion and meiotic recombination, necessary for the recognition of the homologous chromosomes. Here, we review the different actors involved in axial element formation in S. cerevisiae and in mouse. We describe the current knowledge of their localization pattern during prophase I, their functional interdependence, their role in sister chromatid cohesion, loop axis formation, homolog pairing before meiotic recombination, and recombination. We also address further challenges that need to be resolved, to fully understand the interplay between the chromosome structure and the different molecular steps that take place in early prophase I, which lead to the successful outcome of meiosis I.